Fascist aspirants: Fascist Forge and ideological learning in the extreme-right online milieu. (3rd July 2022) - Lee, Benjamin; Knott, Kim
ABSTRACT: Learning in extremist settings is often treated as operational, with little regard to how aspiring participants in extremist settings engage with complex and abstract ideological material. This paper examines learning in the context of the amorphous network of digital channels that compose the extreme-right online milieu. Through an in-depth qualitative analysis, we explore how well the prevailing model of extremist ideological learning (in 'communities of practice') accounts for the behaviour of aspiring participants of Fascist Forge, a now-defunct extreme-right web forum. The findings suggest that some of the social aspects of communities of practice have been replicated in the online setting of Fascist Forge . However, for a combination of technical and ideological reasons, the more directed and nurturing aspects of learning have not. Several issues are raised about the role of ideological learning in online communities, notably the open accessibility of extremist material, the lack of ideological control leading to potential mutation and innovation by self-learners, and the role of digital learning in the preparation, shaping and recruitment of individuals for real world organising and activism.